2002
DOI: 10.1016/s1474-7065(02)00064-5
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary analysis of the groundwater recharge to the Karoo formations, mid-Zambezi basin, Zimbabwe

Abstract: A preliminary analysis of the groundwater recharge to the Karoo formations, midZambezi basin, ZimbabweLarsen, F; Owen, R; Dahlin, Torleif; Mangeya, P; Barmen, Gerhard Link to publication Citation for published version (APA): Larsen, F., Owen, R., Dahlin, T., Mangeya, P., & Barmen, G. (2002). A preliminary analysis of the groundwater recharge to the Karoo formations, mid-Zambezi basin, Zimbabwe. Physics and Chemistry of the Earth, 27(11-22), 765-772. DOI: 10.1016 General rights Copyright and moral rights for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…9(b) -as reported by Butterworth et al (1999). The estimated groundwater recharge of 100 mm year -1 is within the range reported from elsewhere in Zimbabwe by Larsen et al (2002), but somewhat higher than those reported by Farquharson & Bullock (1992), Sibanda et al (2009) or Wright (1992. However, it should be remembered that the modelled season (2007/08) had higher than average rainfall (see Table 3).…”
Section: Modelling Resultssupporting
confidence: 78%
“…9(b) -as reported by Butterworth et al (1999). The estimated groundwater recharge of 100 mm year -1 is within the range reported from elsewhere in Zimbabwe by Larsen et al (2002), but somewhat higher than those reported by Farquharson & Bullock (1992), Sibanda et al (2009) or Wright (1992. However, it should be remembered that the modelled season (2007/08) had higher than average rainfall (see Table 3).…”
Section: Modelling Resultssupporting
confidence: 78%
“…The total chloride deposition from the atmosphere, mainly from precipitation and measured over only two years in the study area, ranged between 0.5 and 1.0 mg/L. Larsen et al (2002) proposed for the total chloride deposition from the atmosphere an average value of 0.5 mg/L for western Zimbabwe. For the computation of the recharges a value of 0.6 mg/L has been used.…”
Section: Analyses and Resultsmentioning
confidence: 91%
“…Larsen et al (2002) predicted for adjoining areas in the Mid Zambezi basin recharge rates on the order of 20-25 mm/year, Obakeng (2007) found for its similar region in northeast Botswana a recharge rate of 15 mm/year, and Beekman et al (1996) adopted recharge values for Botswana in the range of 10-25 mm/year. Comparing with previous recharge studies carried out in the Nyamandhlovu area, it can be concluded that the computed recharge rates under this study are not far off from the estimates by Martinelli and Hubert (1996) ranging from 14 to 28 mm/year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike northern Africa and Europe, positive and near‐zero ∆δ 18 O late‐Pleistocene values exist away from the coasts, including the eastern portion of the Ntane Sandstone aquifer (Botswana; Osenbrück et al, ; Stadler et al, ), the Omatako Basin (northern Namibia; Külls, ) and the Stampriet Aquifer (eastern Namibia; Stute & Talma, ). Other aquifers systems have negative ∆δ 18 O late‐Pleistocene values, such as those in the Kalahari Desert of southern Botswana (Kulongoski et al, ), southwestern Zimbabwe (Larsen et al, ), and the Uitenhage Aquifer located on the southern coast of South Africa (Heaton et al, ), signifying that impacts of deglacial climate changes on the southern Africa's water cycle varied spatially.…”
Section: Paleoclimate Conditionsmentioning
confidence: 99%